PENGUATAN LITERASI: PENINGKATAN KOMPETENSI LITERASI MELALUI OPTIMALISASI PROGRAM LITERASI DI SMK NEGERI 4 JENEPONTO - Abdul Haliq; Nojeng, Asis; Nurhusna, Nurhusna; Baharman, Baharman; Suhardi Rahman, Edi (Jurnal Pengabdian Masyarakat, 2024)
The aim of implementing this activity is to increase literacy competency and interest for teachers regarding the importance of literacy programs in schools to increase vocational school students' literacy interest. This activity was carried out as a form of concern regarding students' low awareness and interest in literacy. There are 4 stages in this activity, namely in the form of analyzing program implementation needs, developing training materials, implementing training, and evaluating activities. Based on the evaluation results during training and post-mentoring, it can be concluded that literacy strengthening activities for SMKN 4 Jeneponto schools have the potential to increase teachers' literacy understanding and awareness in programming literacy activities in schools. Apart from that, based on the results of the activity evaluation, it can be concluded that there has been a significant increase in the number of literacy programs prepared by the school. Apart from that, teacher involvement in literacy programs has also increased so that schools can program literacy agendas to increase literacy awareness, interest and competence for teachers and students.